Atina İstanbul arasında fotografik deneysel bir buluşma = Mia peiramatike photographike synantese dno poleon : Athenaz kai İstampoul = An experimental encounter of photography between two cities : Athens and İstanbul : Merhaba Atina : here İstanbul : kalemera Athena : chaire İstampoul - Özendes, Engin. (İstanbul)
227 s.